2020
DOI: 10.1002/ejlt.202000071
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effects during Physical Refining of Palm Oil to Mitigate the Formation of Monochloropropanediols

Abstract: The aim of this study is to assess the synergy of mitigating main chlorine sources in palm oil and the oil refining conditions in a lab-scale physical refining process. Mitigation concepts including centrifugation and washing steps are integrated into the physical refining protocol and the MCPD levels in the fully refined oils are determined. The endogenous chlorine content of the crude oil and that of the bleaching clay is confirmed to predominantly impact MCPD formation in this refining process. Residual sed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…Recently, Hew et al 34) , reported the effectiveness of using optimal dose of different leaching earth in reducing 3-MCPDE and GE 34) . Strong centrifugation and clay washing are also suggested as an effective means of lowering level of MCPDE content of refine oil 35) . More recently, Oey et al 24) achieved 87% reduction in GE by using double refining with highlow deodorization temperature.…”
Section: Refining Of Crude Palm Oilmentioning
confidence: 99%
“…Recently, Hew et al 34) , reported the effectiveness of using optimal dose of different leaching earth in reducing 3-MCPDE and GE 34) . Strong centrifugation and clay washing are also suggested as an effective means of lowering level of MCPDE content of refine oil 35) . More recently, Oey et al 24) achieved 87% reduction in GE by using double refining with highlow deodorization temperature.…”
Section: Refining Of Crude Palm Oilmentioning
confidence: 99%
“…The purpose of water washing was two-fold: on one hand to reduce the chloride content of the clay as reported previously [27] and on the other hand to reduce the acidity of the clay. This latter was followed by measuring the pH of the washing water obtained from the 10% suspension of the original and washed clays.…”
Section: Methodsmentioning
confidence: 99%
“…Clearly, the acidic conditions either introduced during the degumming process or as a result of high free fatty acid (FFA) content of the crude oil, favor the formation of MCPD and water-based degumming can lead to less MCPD. [16,19,20,26,27] Literature also reports about investigations on the role of the bleaching clay acidity in the formation of these process contaminants, however controversially while some of these studies found mitigation benefits using acid activated clays, [16] others did not. [18] From the theoretical point of view, however, both of these findings may be correct since both the input oil and the bleaching clay contribute to the overall manifested MCPD levels.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations